Walt Disney$1 (Bs Winnie the Pooh and Tigger too.s - Milne, A. A. (Alan Alexander), 1882-1956.; Walt Disney Productions (New York : Random House, 1975)
Rabbit plans to unbounce Tigger, but he discovers he likes a bouncy Tigger best.
Based on stories written by A. A. Milne.
Keywords: Friendship -- Fiction